Keganasan, penipuan & internet - Hishamuddin Rais, 1951-. (Petaling Jaya : SIRD, 2008)
Essays on sociopolitical conditions, cultural life, and technology development in Malaysia.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Koleksi Sumbangan: Dr. Mohamad Nasrin Mohamad Nasir.
Keywords: Hishamuddin Rais, -- 1951 -- Views on politics; Malaysia -- Politics and government